THE CORRECT NAME FOR PYRROSIA HASTATA CHING (POLYPO- DIACEAE, PTERIDOPHYTA) - Veldkamp, Jan Frits (Research Center for Biology, 2004)
VELDKAMP, J.F. 2004. The correct name for Pyrrosia hastate Ching (Polypodiaceae, Pteridophyta). Reinwardtia 12 (2): 191 -193. Pyrrosia hastata Ching (Polypodiaceae, Pteridophyta) is based on Acrostichum hastatum Thunb.(1784) non Houtt. (1783). Its correct name is P. tricuspis (Sw.) Tagawa.